Influencia de la efectividad en el desarrollo social de los niños y niñas de 3 a 5 años de la corporación análisis y proyecciones de la parroquia Tendales, cantón El Guabo, durante el periodo 2013-2011. - Suárez Borbor, Eva Virginia (2011)
Family to be considered as the basis of society and parents as important in the lives of their children part, plays a vital role in the emotional development of children, so that failure this main axis empienza a chain of q conflicts not being confronted, it will trigger serious problems and consequences.